Photovoltaic properties of benzotriazole containing alternating donor-acceptor copolymers: Effect of alkyl chain length - Baran, Derya; Balan, Abidin; Stubhan, Tobias; Ameri, Tayebeh; Toppare, Levent; Brabec, Christoph (Synthetic Metals, 2012)
A series of variable alkyl chain length substituted donor-acceptor (D-A) conjugated polymers with thiophene ring as the donor and benzotriazole moiety as the acceptor has been investigated in bulk heterojunction solar cells. The optical and electrochemical properties showed that the absorption onsets and the energy levels of the copolymers were not affected by alkyl substitution revealing 1.9 eV of optical band gap. The morphologies of the blend film can be fine-tuned by increasing the chain length attached to the benzotriazole unit. Photovoltaic devices were fabricated using (6,6)-phenyl-C-butyric acid methyl ester (PCBM) and (6,6)-phenyl-C-butyric acid methyl ester (PCBM) as the acceptors. The maximum performance was achieved with a V of 0.75 V, J of 3.70 mA/cm , FF of 45% and a PCE of 1.23% for the PTBT-DA10:PCBM device using 1:4 w/w ratio in chlorobenzene (CB). © 2012 Elsevier B.V. All rights reserved.
Keywords: Benzotriazole; Donor-acceptor polymers; Effect of chain length; Organic photovoltaics; Solar cell